Job‐to‐Job and Job‐to‐Nonemployment Turnover by Gender and Education Level - Royalty, Anne Beeson (Journal of Labor Economics, 1998)
Using multinomial probit estimates of the probability of job‐to‐job and job‐to‐nonemployment turnover, I find that differences between women's and men's turnover are due to the behavior of less educated women. Both the job‐to‐job and job‐to‐nonemployment turnover of less educated women are significantly different from that of more educated women as well as both groups of men. I also find that distinguishing between types of turnover—job‐to‐job versus job‐to‐nonemployment—is quite important, particularly in understanding the turnover patterns of women.